Nursing of a child with biliary-enteric anastomotic strictures complicated by intestinal obstruction after liver transplantation (1例肝移植术后并发胆肠吻合口狭窄与肠梗阻患儿的护理) - DI Mengxue (邸梦雪); JIANG Ying (蒋莹); GAO Wei (高伟) (Association of Integrative Nursing, 2023)
This article summarizes the nursing experience of a child with biliary-enteric anastomotic strictures complicated by intestinal obstruction after liver transplantation. Nursing priorities include timely understanding of the changes in the child's condition during follow-up, and rapid cooperation with interventional treatment; Cooperating with doctors to effectively relieve intestinal obstruction, restoring gastrointestinal function, and improving the feeding compliance of the child's family; Standardizing pipeline and fistula care, monitoring nutritional risks, and reasonably providing nutritional support; Developing a multi-platform practice continuity nursing model to ensure an efficient quality of life for transplanted children. (总结1例肝移植术后并发胆肠吻合口狭窄与肠梗阻患儿的护理经验。护理重点包括: 及时了解患儿随访时病情变化, 迅速配合介入治疗; 配合医生有效解除肠梗阻, 恢复胃肠功能, 提高患儿家属喂养依从性; 规范管路与瘘道护理, 监测营养风险, 合理提供营养支持; 发展多平台实践延续性护理模式, 保证移植患儿的高效生活质量。)